Myoepithelial Carcinoma Arising in a Plasmacytoid Myoepithelioma of the Parotid Gland Synchronized with Melanoma: A Case Report and Review of the Literature - Soberanis-Piña, Pamela Denisse (Case Rep Oncol, 2021)
Myoepithelial carcinoma, also known as malignant myoepithelioma, is considered an extremely rare (0.45–1%) malignant salivary gland neoplasm. Approximately 100 cases have been reported in the English-language literature on myoepithelial carcinoma. The majority of the myoepitheliomas described in the literature have been benign, and the malignant counterpart is considered rare (<1%). Such a tumor may appear de novo or rarely develop from a preexisting pleomorphic adenoma (<20%), and in exceedingly rare cases (<0.5%), it has arisen from a benign myoepithelioma (i.e., plasmacytoid myoepithelioma). To our knowledge, no case of myoepithelial carcinoma of the parotid gland arising in a plasmacytoid myoepithelioma synchronized with melanoma has been reported to date. The treatment of myoepithelial carcinoma has been mainly surgical, including wide excision with free margins, with or without nodal dissection. The roles of chemotherapy and radiotherapy have not yet been established. We report a case of myoepithelial carcinoma of the parotid gland arising in a plasmacytoid myoepithelioma synchronized with melanoma in a 40-year-old woman. In our case, a complete response was achieved with surgery followed by adjuvant chemotherapy based on carboplatin and paclitaxel concurrent with radiotherapy.